The fake news phenomenon - Harris, Duchess (News literacy., 2018)
Traces the history of fake news back 1,500 years, and explores its causes and effects. Also discusses how newspapers and television news channels can give facts while still having bias. Offers tips for identifying fake news. Includes color photographs, critical thinking questions, a glossary, and further resources.